Occurrence and characteristics of patients with de novo advanced breast cancer according to patient and tumor characteristics – A retrospective analysis of a real world registry. (September 2022) - Müller, Volkmar; Hein, Alexander; Hartkopf, Andreas D.; Fasching, Peter A.; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Beckmann, Matthias W.; et al.
Abstract: Background: Patients with de novo metastatic breast cancer (dnMBC) may have different clinical and pathological characteristics. In studies concerned with first-line metastatic patients, the proportion of these patients without secondary resistance mechanisms may have a large influence ont the study results. The aim of this study was to identify patient and tumor characteristics that are associated with dnMBC vs. recurrent MBC (rMBC). Methods: This is a retrospective analysis of data prospectively collected in the PRAEGNANT metastatic breast cancer registry (NCT02338167). Firs line treated patients were eligible. Patient and tumor characteristics were compared with common disease and tumor characteristics relative to de novo metastatic status, as well as early and late recurrences after primary disease without metastases. Results: Among the 947 patients identified, 355 were included with de novo metastatic disease (37.5%). Older age and HER2-positive disease were significantly associated with a higher frequency of dnMBC. Patients younger than 50, 50–69, or 70 years or older had dnMBC frequencies of 22.7%, 44.0%, and 57.6%, respectively. HER2-positive patients had dnMBC at initial presentation in 49.1% of cases, in comparison with 21.9%, 35.5%, and 37.6% in patients with triple-negative, luminal A–like and luminal B–like breast cancer, respectively. Conclusion: Age and breast cancer subtype are associated with the frequency of first-line MBC patients. Inclusion criteria concerning age or breast cancer subtype can influence the frequency of these patients in a selected patient population and can therefore modify the number of patients with secondary resistance to specific therapies in clinical trials. Highlights: Tumor and patient correlates of de novo metastatic (dnMBC) vs. recurrent 1st line metastatic breast cancer patients from PRAEGNANT registry are analyzed. HER2 positive patients have most often and triple negative patients least often dnMBC. dnMBC should be considered conducting and interpreting clinical trials results.